Linking habitat characteristics and juvenile density to quantify Salmo salar & Salmo trutta smolt production in River Sävarån, Northern Sweden - Molin, Johan (2008)
Even though the European Union has set up goals for rivers that support wild salmon to reach a production that is 50% of the MAXIMUM natural potential, there is a general lack of knowledge about the production capacity of salmonids in Sweden. To estimate the production of salmon and sea trout in the Sävarån river, I combined habitat mapping with available electro-fishing data. Additionally the smolt run was enumerated (with screw-traps) and radio-tracking of migrating spawners was performed. In the river's main branch I found 51 ha potential spawning and nursery habitats. With present juvenile densities, these areas should be able to produce 1300-7580 salmon smolt and 635-3544 trout smolt, in agreement with screw-trap data in the years 2005-2007. A hypothetical maximum production of c. 18400 salmon smolt was also calculated. Telemetry showed that at the time of spawning the radio-tagged adult fish were situated in or close to potential spawning areas that were defined during the habitat mapping.